2016
DOI: 10.1016/j.tra.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Airport capacity choice under airport-airline vertical arrangements

Abstract: This study investigates the effects of airport-airline vertical arrangements on airport capacity choices under demand uncertainty. A multi-stage game is analyzed, in which competing airlines contribute to capacity investments and at the same time share airport revenues. Our analytical results suggest that for a profit-maximizing airport, such a vertical arrangement leads to higher capacity although its profit may not be higher. For a welfare-maximizing airport, such an arrangement has no effect on capacity or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…If the airport might respond to this revenue decrease with a reduction of their operational or capacity holding cost, the effect on investment size would be tempered, since this response has a negative impact on the investment size. As opposed to Xiao, Fu, and Zhang (2016) who do not consider investment timing and who show that cost savings lead to larger expansion, we find cost savings leading to smaller expansion due to the timing anticipation.…”
Section: Conclusion and Future Researchcontrasting
confidence: 88%
See 1 more Smart Citation
“…If the airport might respond to this revenue decrease with a reduction of their operational or capacity holding cost, the effect on investment size would be tempered, since this response has a negative impact on the investment size. As opposed to Xiao, Fu, and Zhang (2016) who do not consider investment timing and who show that cost savings lead to larger expansion, we find cost savings leading to smaller expansion due to the timing anticipation.…”
Section: Conclusion and Future Researchcontrasting
confidence: 88%
“…In addition, the authors considered capacity and pricing as sequential instead of simultaneous decisions. Xiao, Fu, and Zhang (2016), Xiao et al (2017) incorporated airport-airline vertical arrangements and airline competition in their RO models to analyse airport capacity investment under demand uncertainty, without considering the option of flexible timing.…”
Section: Airport Infrastructure Investments: a Literature Reviewmentioning
confidence: 99%
“…RD is a complicated process, and some airports have to use multiple incentives to entice airline cooperation [1,20,26]. Studies under the airport-airline arrangements context have shown the positive impacts of incentives on airport-airline collusion [27][28][29][30]. Such studies, however, cannot fully explain the increasing use of incentives for RD in the airport industry and the systematic process of RD, including the formulation, implementation, and performance estimation.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of convenient and frequent international travel, more airports are reaching capacity for passenger transport, leading to severe delays and traffic congestion at airports and jeopardizing the long-term development of the aviation sector [3]. At the end of July 2013, Taoyuan International Airport Corporation (TIAC) completed its expansion of Terminal 1, which can accommodate 15 million passengers.…”
Section: Introductionmentioning
confidence: 99%